PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA KERJA TERHADAP KINERJA GURU SD NEGERI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Susanto, Edy; A.M, Juhri; Badrun, M. (STAI Darul Qalam Tangerang, 2025)
This study aims to determine the effect of the principal's leadership style and work culture on the performance of public elementary school teachers in Gadingrejo District, both partially and simultaneously. The approach used is quantitative associative with survey method. Data were collected through closed questionnaires from 108 teachers selected by proportional randomization. Respondents were permanent teachers with at least two years of teaching experience. The research instruments were developed based on indicators of three variables: leadership style (instructive, consultative, participative, delegative), work culture (collegiality, trust, openness, appreciation, work habits), and teacher performance (planning, implementation, evaluation, classroom management, and professional development). Analysis was conducted descriptively and inferentially using multiple linear regression.The results showed that leadership style and work culture had a significant effect on teacher performance, both individually and collectively. A participative leadership style and a supportive work culture can create a productive work environment. The findings recommend the importance of strengthening principal leadership and developing work culture as strategies to improve the quality of teacher performance in elementary schools.